2013
DOI: 10.12740/pp/18177
|View full text |Cite
|
Sign up to set email alerts
|

Sense of humour in schizophrenia – ability of humour reception and possibilities of its application in therapeutic interventions

Abstract: The existing research on sense of humour in schizophrenia is focused on two main areas, mainly, assessment of patients' abilities to understand and appreciate humour and denoting the possibilities of its application in therapeutic programs concentrating on the improvement of patients' functionality and preventing illness relapses. The vast majority of the conclusions from the above mentioned research corroborate the opinion on the usefulness of developing and reinforcing sense of humour in schizophrenia, empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In other words, it will be influenced by many factors such as cognitive function and personal traits (Dixon, 1980;Wellenzohn, Proyer, & Ruch, 2018). Some studies (Bozikas et al, 2007;Parnowska, Braniecka, & Radomska, 2013) indicated low reception of humour in schizophrenia does a negative impact on the effectiveness of the intervention. Likewise, one study (Thaler et al, 2012) showed that people with dementia have a lower sense of humour than normal people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it will be influenced by many factors such as cognitive function and personal traits (Dixon, 1980;Wellenzohn, Proyer, & Ruch, 2018). Some studies (Bozikas et al, 2007;Parnowska, Braniecka, & Radomska, 2013) indicated low reception of humour in schizophrenia does a negative impact on the effectiveness of the intervention. Likewise, one study (Thaler et al, 2012) showed that people with dementia have a lower sense of humour than normal people.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of neurocognitive function, it may lead to a poor intervention for the reason that patients with mental disorders usually have poor humour comprehension. However, many studies emphasize its beneficial effects on people with schizophrenia, such as reducing depression, anxiety, and aggression and improving life satisfaction (Cai et al, ; Parnowska et al, ). Therefore, future research should consider the sense of humour of the participants and apply humour skills appropriately to confirm the benefits and disadvantage of humour intervention in patients with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is plenty of evidence showing that the ability to feel mixed emotions may be considered a developmental achievement attained over the entire lifespan and may be especially beneficial to quality of life [54] – [56] . Consequently, individuals who have failed in coping with an emotional crisis that resulted in psychiatric hospitalization, showed lower ability to experience positive and negative affects within one emotional state when confronted with affectively complex stimuli, such as ambivalent jokes, than the healthy control group [57] , [58] . Thus, individuals disposed to feel mixed emotions in adverse situations seem to cope more efficiently than others because they experience positive affect in combination with the negative emotional states caused by a stressful event, which may provide emotional comfort.…”
Section: Studymentioning
confidence: 99%
“…With the exception of some pathological cases involving schizophrenia and depression (Ivanova 2014;Parnowska 2013), almost everyone is disposed to laugh at or find humorous at least some things. In this minimal, descriptive sense, almost everyone has a sense of humor.…”
Section: The Philosophy Of Humormentioning
confidence: 99%